Brand Communication as Cultural Production: a Sociological Study of Advertising on Social Media - Okza Hendrian Wijaya; Muhammad Arrozi; Yurdan Vebry Endika; Andre Rahmat Kurniawan; Muhammad Afdhal (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This thesis examines the relationship between brand communication and cultural production, with a particular focus on advertising practices on social media platforms. It develops a theoretical framework that integrates perspectives from cultural production theory, the sociology of advertising, and the conceptualization of social media as a cultural space. Using a qualitative research design, the study analyzes advertising as a form of cultural practice that actively shapes consumer identities. The findings demonstrate that social media significantly transforms branding strategies and consumer behavior by enabling interactive, symbolic, and identity-driven forms of communication, as evidenced by selected case studies of prominent advertising campaigns. This research contributes to a deeper understanding of advertising as a dynamic cultural phenomenon and offers insights for future studies on brand communication in digitally mediated cultural environments.